144 Atrial and ventricular phenotypes in a cohort of patients with functional tricuspid regurgitation: clinical, echocardiographic, and prognostic aspects. (8th December 2021) - Gavazzoni, Mara; Heilbron, Francesca; Florescu, Denisa; Ciampi, Pellegrino; Guta, Andrada C; Ochoa, Roberto; Tomaselli, Michele; Volpato, Valentina; Oliverio, Giorgio; Caravita, Sergio; Parati, Gianfranco; Muraru, Denisa; et al.
Abstract: Aims: Atrial functional tricuspid regurgitation (A-FTR) has emerged as a newly recognized phenotype of functional tricuspid regurgitation (FTR), occurring in patients with atrial fibrillation and right atrial (RA) dilation but normal right ventricular (RV) size and function. Its prevalence, echocardiographic features, and prognosis have not yet clarified since most evidence to date has included indiscriminately FTR patients with A-FTR and ventricular form (V-FTR). Aim of this study was to investigate the differences between these two phenotypes of FTR in terms of clinical correlates, echocardiographic aspects, and prognosis. Methods and results: A total of 180 consecutive patients with moderate to severe FTR referred for echocardiography in two Italian centres were retrospectively enrolled. A-FTR was defined as: (1) longstanding atrial fibrillation; (2) PASP <50 mmHg; (3) left ventricular ejection fraction > 60% (complete according to the ACC guidelines); and (4) no significant left side valve disease. 3D TTE was used for the quantitative assessment of TR and chamber sizing and function. The composite endpoint of death for any cause and heart failure (HF) hospitalization was used as primary outcome of this analysis; secondary endpoint was HF-hospitalization. Patients with A-FTR were 30% of the population; they were older than those one with V-FTR; with higher systolic blood pressure and less advanced symptoms. Chronic obstructive pulmonary disease was more prevalent in V-FTR. Patients with V-FTR had larger 3D-derived right ventricle (RV) volumes, both diastolic and systolic, while right ventricle ejection fraction (RVEF) was similar. RV functional parameters as TAPSE, RVFWLS, and RVGLS were significantly lower in the V-FTR patients as well as all the parameters of RV-pulmonary arterial (PA) coupling. After a median follow-up of 24 months (IQR: 2–48), 72 patients (40%) reached the primary endpoint and 64 (36%) hospitalized for HF. The rate of composite endpoint tended to be lower in A-FTR than in V-FTR (29% vs. 44%, P -value: 0.1); the rate of hospitalization for HF was higher in V-FTR patients (22% vs. 41%, P -value: 0.04). Correlates of combined endpoint in both groups were: functional class of dyspnoea (NYHA class III–IV vs. I–II), severe TR grade (HR in V-FTR: 2.88 [1.63–5.06], P < 0.01; HR in A-FTR: 8[3–17], P < 0.01); RV volumes, RA volumes. Estimated SPAP as well as all the parameters of RV function and of RV-PA coupling were correlates of prognosis only in V-FTR; conversely, parameters of TA dimensions were related to combined Endpoint in A-FTR phenotype, while RV function and RV-PA coupling indexes did not. Conclusions: Patients having A-FTR have an incidence of combined endpoint slightly different, without reaching a statistically significant difference, thus remarking the fact that A-FTR could not be considered 'more benign' and should therefore be targeted. Prognostic predictors are different between A-.FTR and V-FTR patients.